2004
DOI: 10.1353/sof.2005.0019
|View full text |Cite
|
Sign up to set email alerts
|

Corn, Klansmen, and Coolidge: Structure and Framing in Social Movements

Abstract: This article examines how structural conditions and social movement frames interactto influence mobilization and political consequences 01 social movements.Mobilization efforts benefit when movement framing is congruent with localstructural conditions. This mobilization, in turn, produces politicalleverage for the movement through its capacity to deliver support of its members and adherents. Its political advantage may be offtet, however, if another of its key framing activities, the construction ofcollective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 61 publications
0
57
0
Order By: Relevance
“…Racist organizations often appeal to the economic interests of potential recruits, arguing that foreigners or members of racial and ethnic minority groups pose a threat to their livelihood (Dobratz and Shanks-Meile, 1997;McVeigh, 2004). They point to affirmative action, free trade agreements, or other policies and legislation, as evidence for their belief that the U.S. government is more concerned with the rights of foreigners, immigrants, or minority group members than with the rights of White Americans (Dobratz and Shanks-Meile, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Racist organizations often appeal to the economic interests of potential recruits, arguing that foreigners or members of racial and ethnic minority groups pose a threat to their livelihood (Dobratz and Shanks-Meile, 1997;McVeigh, 2004). They point to affirmative action, free trade agreements, or other policies and legislation, as evidence for their belief that the U.S. government is more concerned with the rights of foreigners, immigrants, or minority group members than with the rights of White Americans (Dobratz and Shanks-Meile, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A flawed diagnosis and a misguided prognosis of a particular problem can still motivate action if the diagnosis and prognosis seem plausible. The resonance of a collective action frame is partly determined by local conditions that can restrict access to information that could challenge the credibility of the frame (McVeigh et al, 2003;McVeigh, 2004). We argue that contemporary racist groups' framing of a wide variety of social issues should resonate most strongly where non-White individuals are constrained to the position of the stranger.…”
Section: Framing the Strangermentioning
confidence: 92%
See 1 more Smart Citation
“…Framing disputes may be fundamentally tactical in nature. Within a coalition, participants may fear that the use of a particular frame will direct attention away from their issues or concerns (Babb, 1996;Benford, 1993), overextend the movement in a way that dilutes its strength (Snow & Benford, 1988, p. 206), or create backlash by the opposition (Zald & Useem, 1987;McVeigh, Myers, & Sikkink, 2004;Meyer & Staggenborg, 1996). Participants in a countermovement may fear that a particular frame will allow the movement to convey its false messages effectively or otherwise mislead the public (Evans, 1997).…”
Section: Place and Framing In Social Movementsmentioning
confidence: 99%
“…Researchers have called to examine the interconnections between these different areas to understand how structure and agency both influence social change (Meyer, 2002). Empirical research has found that framing is most effective when it fits within the political opportunity structures (McVeigh, Myers, & David, 2004). Others have found that the actors in social movements shape and change frames as movements develop and tactics change (Holland, 2009;Ryan & Gamson, 2006).…”
Section: Social Movements: Political Process Resources Framing Andmentioning
confidence: 99%